The bona fide investor corporate nationality and treaty shopping in investment treaty law - Foote, Simon (International arbitration law library ;, 2022)
"Many corporations engage in treaty shopping - or 'nationality planning'- to procure investment treaty protection by attainment of a nationality of convenience. This book is the first in-depth exploration of a substantive legal basis by which to assess the bona fides of a corporate investor's identity in a convenient jurisdiction: i.e., examination of the purpose for which a corporate exists in the ownership structure of the relevant investment. In a comprehensive review of the concept of treaty shopping, the author examines the degree to which manipulation of corporate nationality is consistent with the objects and purposes of the investment treaty regime, and analyses its effect on the legitimacy of investor-state dispute mechanisms. To evaluate a substantive test for a bona fide investor, the book looks to analogous areas of international law such as the law of diplomatic protection and double tax treaties, and reviews in detail the relevance in investment treaty law of such pertinent issues and topics as the following: the concept of separate legal personality; abuse of the corporate form at municipal law; the role of Article 25 of the ICSID Convention; the approach to the nationality of natural persons; the approach to the jurisdictional concept of an 'investment'; criteria used to connote corporate nationality; the concept of the commercial purpose of the corporate investor claimant; the concept and limits of the principle of abuse of right at international law; and the application of, and the relationship between, the four tenets of Article 31(1) of the Vienna Convention: ordinary meaning, good faith, context, and object and purpose. The effectiveness of substantive criteria presently used to mitigate illegitimate or undesirable treaty shopping are examined and compared with the 'purpose to exist' test, and the prospective legal mechanisms that may be utilised to implement a substantive approach are canvassed in detail. This incomparable book brings coherence - and indeed a solution - to the debate about the attribution and use of nationality by corporations in the field of investment treaty law. It is a giant step towards legal certainty as to the need for, and the means by which, limits can be placed on investment treaty jurisdiction for corporate entities. It will be of immense interest to practitioners who advise on jurisdictional issues for clients (whether states or investors) and debate jurisdictional concepts and corporate nationality issues before international tribunals. It will also be a useful resource, and a challenge, to arbitrators regarding the extent to which investment treaty tribunals tolerate manipulation of corporate nationality and circumscribe jurisdiction to protect the legitimacy of the investment treaty system"--